Single-Cell RNA Sequencing Atlas From a Bivalve Larva Enhances Classical Cell Lineage Studies - Salamanca-Díaz, David A.; Schulreich, Stephan M.; Cole, Alison G.; Wanninger, Andreas (Frontiers in Ecology and Evolution, 2022)
Ciliated trochophore-type larvae are widespread among protostome animals with spiral cleavage. The respective phyla are often united into the superclade Spiralia or Lophotrochozoa that includes, for example, mollusks, annelids, and platyhelminths. Mollusks (bivalves, gastropods, cephalopods, polyplacophorans, and their kin) in particular are known for their morphological innovations and lineage-specific plasticity of homologous characters (e.g., radula, shell, foot, neuromuscular systems), raising questions concerning the cell types and the molecular toolkit that underlie this variation. Here, we report on the gene expression profile of individual cells of the trochophore larva of the invasive freshwater bivalve Dreissena rostriformis as inferred from single cell RNA sequencing. We generated transcriptomes of 632 individual cells and identified seven transcriptionally distinct cell populations. Developmental trajectory analyses identify cell populations that, for example, share an ectodermal origin such as the nervous system, the shell field, and the prototroch. To annotate these cell populations, we examined ontology terms from the gene sets that characterize each individual cluster. These were compared to gene expression data previously reported from other lophotrochozoans. Genes expected to be specific to certain tissues, such as Hox1 (in the shell field), Caveolin (in prototrochal cells), or FoxJ (in other cillia-bearing cells) provide evidence that the recovered cell populations contribute to various distinct tissues and organs known from morphological studies. This dataset provides the first molecular atlas of gene expression underlying bivalve organogenesis and generates an important framework for future comparative studies into cell and tissue type development in Mollusca and Metazoa as a whole.